Empowering Adolescent Girls Through Social Organisation-Based Mentoring to Prevent Malnutrition - Khafidhoh, Nur; S.A. Nugraheni; Sriatmi, Ayun; Winarni, Sri (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: Adolescent girls are prone to nutrition-related problems, ranging from anaemia, SEZ, undernutrition and overnutrition. Currently, more interventions are conducted on school-aged adolescents, while adolescents who are no longer in school have not been addressed. Implementation of interventions in the community, such as youth organisations and religious organisations, not only in schools. This can increase accessibility and participation among adolescents who are not in formal education young women-based social organisations can be involved in interventions to prevent adolescent malnutrition through a mentoring model. The aim of this study was to analyse the effect of organisation-based mentoring on improving knowledge, this study aims to analyse the differences in knowledge, practice of malnutrition prevention in the form of measurement of calorie adequacy and iron intake. Methods: This research design is a quasi-experimental pre and post-test with a control group. This study was conducted on 189 adolescent girls, which were divided into an intervention group of 98 people and a control group of 91 people. Respondents were taken by purposive sampling based on inclusion criteria. The study was conducted for 10 weeks. Data were obtained by structured interviews. Data were analysed using paired t test and wilcoxon, while between group analysis with manwithney. Results: The results showed that there was a difference between knowledge, behaviour before and after the intervention between the treatment group and the control group with p < 0.05. There was a significant increase in knowledge, attitude and behaviour in the intervention and control groups. Conclusion: Community organisation-based mentoring has been shown to be effective in improving adolescent health. It is necessary to strengthen regulations in regulating the role of community organisations, especially adolescents, through structured assistance and education for vulnerable groups including adolescents. The results of the study can be duplicated to be implemented in other organisations that focus on adolescents.